Moving Beyond G‐CSF Mobilization—Learning From a 15‐Year Experience of Different Stem Cell Mobilization Regimens in Multiple Myeloma - Sumeet Mirgh; Bhausaheb Bagal; Sachin Punatar; Anant Gokarn; Nishant Jindal; Akanksha Chichra; Lingaraj Nayak; Sumathi Hiregoudar; Minal Poojary; Suryatapa Saha; Sarika Parab; Shashank Ojha; et al. (Cancer Medicine)
ABSTRACT Background Stem‐cell mobilization in multiple myeloma is usually done with G‐CSF with or without Cyclophosphamide (Cy) based chemotherapy/Plerixafor. Pre‐clinical data suggest the role of proteasome inhibitors in mobilization. We previously reported that Bortezomib (Bort) when added to a Cy‐based regimen had a better stem‐cell yield. Consequent to favorable results with Bort + Cy‐G‐CSF, we used Bortezomib with G‐CSF too. Hence, four different mobilization regimens were used—Bort + G‐CSF (Group‐1); G‐CSF + Plerixafor (Group‐2); Bort – Cy‐G‐CSF (Group‐3); Cy + G‐CSF (Group‐4). We report here our 15‐year retrospective analysis of these 4 mobilization regimens. Objectives Primary objective was to determine proportion of patients with CD34+ dose ≥ 5 × 106/kg in first apheresis in various groups. Secondary objectives were to determine median CD34+ dose (×106/kg) in first apheresis, total median CD34+ dose (×106/kg) of all harvests and frequency of mobilization failure. Mobilization failure was defined as total CD34+ dose of < 2 × 106/kg or abandoned harvest attempt at physician's discretion after anticipating a poor collection. Results All consecutive patients with MM aged 18–65 years who underwent stem‐cell mobilization from September 2007–December 2022 were included. In an intention‐to‐treat analysis, a total 200 patients with 205 mobilization attempts were analysed. The median age of the cohort was 48 years. The percentage of patients who collected ≥ 5 × 106 CD34+ cells/kg in the first apheresis was 26%, 53%, 69%, and 63% in Groups 1–4, respectively (p = 0.0001). The median CD34 yield in the first harvest (×106/kg) was 3.62, 5.20, 6.04, and 6.05 in Groups 1–4, respectively (p = 0.00004). The median total stem‐cell dose collected (×106/kg) was 5.73, 6.17, 9.14, and 8.23 in Groups 1–4, respectively (p < 0.00001). Mobilization failure rates were 7%, 3%, 0%, and 2%, respectively (p = NS). Conclusion Cyclophosphamide‐based chemo‐mobilization regimens with or without Bortezomib have the advantage of higher total stem‐cell yield, while they are equivalent to G‐CSF + Plerixafor for harvest in a single apheresis. The addition of Bortezomib to Cyclophosphamide may help to increase stem cell yield.